Violence against children and adolescents: the importance of knowledge of the spectrum of bruise colors in its diagnosis - Lara Maria Herrera; Mônica da Costa Serra; Clemente Maia da Silva Fernandes (Revista Sul-Brasileira de Odontologia, 2014)
One of the violence types more observed against children is the physical abuse, which produces many types of traumatic injuries. Contusions are common trauma signs and may indicate aggression when frequently present in locations where accidental injuries are rare. Contusions in skin undergo color changes with the passage of time, and such change in color is called “spectrum of bruise colors of Legrand du Saulle”. Thus, it is possible to estimate the age of the lesion based on the evaluation of color. Injuries caused by child abuse often reach regions of head, face and neck, because they are exposed and easily accessible. Therefore, the dentist is responsible with regard to the diagnosis and the actions to be undertaken against the cases of child abuse. Objective: To present and discuss the significance of the spectrum of bruise colors as a considerable visible trace in suspicion of violence against children and adolescents, during dentists’ clinical routine. Literature review: The study of the “spectrum of bruise colors of Legrand du Saulle” refers to the estimation of the age of the injury, in respect to the color change. The application of this study is of great value for identify if a lesion occurred from a single incident or from multiple incidents, especially in cases where it occurs in the same region of the body, indicative of repetitive trauma. Conclusion: The spectrum of bruise colors is very important for health professionals, such as dentists, for the identification or suspicion of cases of abuse against children and adolescents. As great part of the lesions originated of abuse involve the areas of head and neck, it is unacceptable that these professionals are unaware of the basic signs to help in early diagnosis, which is the case of the colors of the lesions. However, concerning the chronology of the spectrum of bruise colors, it is not possible to establish rigorous times.